A checklist of beetles (ORDER: COLEOPTERA) from Sarikei, Sarawak, Malaysia - Siti Nurlydia Sazali,; Tan, Wei Lim; Nurfarida Anum Zainaddin,; Zulrafie Hambri,; Molujin, Annette Aurelia; Farah Nabillah Abu Hasan Aidil Fitri,; Ratnawati Hazali,; Nuha Loling Othman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
A biodiversity survey to document assemblages of beetles was conducted at Sarikei town, Sarawak, Malaysia from 28th August 2021 to 5th September 2021. A combination of active (hand-picking and aerial netting) and passive (modified Pennsylvanian light trap, baited trap and flight-intercept trap) methods were used during the eight days of sampling, covering areas of mixed dipterocarp forest, mangroves and a recreational park. As a result, a total of 440 individuals, representing 146 species from 49 subfamilies and 23 families of beetles were successfully recorded. In general, Scarabaeidae was reported as the most diverse and abundant family with 46 species (31.51%), followed by Tenebrionidae with 15 species (10.27%), Chrysomelidae with 13 species (8.90%), Carabidae with 12 species (8.22%), and Elateridae (7.53%) with 11 species, respectively. In terms of individual count, the most dominant species was recorded by the scarab beetles of Apogonia destructor (Melolonthinae) with 32 individuals (7.27%). In conclusion, this study provides baseline data for identifying potential biodiversity hotspot areas for future management and conservation action plans in Sarawak.